2017
DOI: 10.1002/ajmg.a.38163
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial phenotypic variability in a Polish family with Sensenbrenner syndrome and biallelic WDR35 mutations

Abstract: Sensenbrenner syndrome (cranioectodermal dysplasia, CED) is a very rare autosomal recessive ciliopathy. Cranioectodermal dysplasia is characterized by craniofacial, skeletal, and ectodermal abnormalities. About 50 patients have been described to date. Sensenbrenner syndrome belongs to a group of ciliary chondrodysplasias and is a genetically heterogeneous disorder. Mutations in five genes: IFT122, WDR35, IFT43, WDR19, and IFT52 have been associated with CED. All known genes encode proteins that are part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 11 publications
3
24
0
Order By: Relevance
“…Each of the unaffected parents is a carrier of one of the aforementioned variants. The missense substitution p.(Asp841Val), identified in the proband has been previously described in a heterozygous state in a female Polish patient with Sensenbrenner syndrome (Walczak‐Sztulpa et al, ). The presence of this variant in the second Polish family with CED indicated that the p.(Asp841Val) change could be a founder mutation in the Polish population.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Each of the unaffected parents is a carrier of one of the aforementioned variants. The missense substitution p.(Asp841Val), identified in the proband has been previously described in a heterozygous state in a female Polish patient with Sensenbrenner syndrome (Walczak‐Sztulpa et al, ). The presence of this variant in the second Polish family with CED indicated that the p.(Asp841Val) change could be a founder mutation in the Polish population.…”
Section: Discussionmentioning
confidence: 80%
“…Less than 60 patients with Sensenbrenner syndrome have been described to date (Antony et al, 2017). The phenotypic spectrum among the patients with Sensenbrenner syndrome is variable, with some intrafamilial and interfamilial differences (Caparr os-Martín et al, 2015;Mill et al, 2011;Walczak-Sztulpa et al, 2017). The biallelic variants identified in six known genes associated with Sensenbrenner syndrome (IFT122, WDR35, IFT43, WDR19, IFT52, and IFT140) are not phenotypically distinct (Arts & Knoers, 2013;Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this family, the identified CNV also comprises part of the neighboring WDR49 , which encodes a member of the WD repeat protein family. Members of this family are involved in a variety of cellular processes, including cell cycle progression, signal transduction, and apoptosis (Walczak‐Sztulpa et al., ), but no functional information have been annotated for WDR49 to date. Therefore, the biological effect of WDR49 loss‐of‐function remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%